Real-Time Ethanol Monitoring System for Palm Sap Fermentation Using a MiCS-5524 Gas Sensor and Arduino Uno - Dini Rizqi Dwi Kunti Siregar; M Syukri Surbakti; Fadhli; zakaria; Susilawati; Hikmal Akbar (Talenta Publisher, 2026)
This study aims to develop a real-time alcohol monitoring instrument for palm sap fermentation using the MiCS-5524 gas sensor integrated with an Arduino Uno. The system consists of the MiCS-5524 sensor, an Arduino Uno microcontroller, and a 16×2 I2C LCD for real-time display. Sensor calibration was performed using ethanol solutions at 10%, 20%, 30%, 40%, 50% and 60% to establish a linear regression model relating sensor resistance to ethanol concentration. Fermentation monitoring was carried out for 72 hours, with measurements taken every 24 hours. Sensor outputs were converted from ADC values into voltage, resistance, and ethanol concentration using the calibration equation. The calibration yielded a strong linear correlation (R² = 0.982). Fermentation tests showed a consistent increase in ethanol concentration, reaching 53.9% after 72 hours. Comparison with a digital alcohol meter produced relative errors ranging from 2.8% to 6.4%, demonstrating good accuracy, low drift, and stable sensor response. Overall, the developed instrument effectively measures ethanol concentration in palm sap fermentation in real time. Its simple configuration, low cost, and reliable performance make it suitable for small-scale palm sap processing, quality control, and laboratory applications. Further improvements, such as environmental compensation and IoT-based monitoring, are recommended to enhance system performance.